Modelling the sediment dynamics of a developing coastal estuary the case of Batan Bay, Aklan - Santos, Franz D.; Herrera, Eugene C.; Hernandez, Bryan Clark B.; Dela Cruz, Gene Euclid T.; Almarza, Hanz Detriech M.; Basina, Ryan M.; Yoshikai, Masaya; Nadaoka, Kazuo (2024)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/9721/8576
Keywords: Aquaculture; Sediments; Sustainability